Bioflocculation Activity in Harvesting System: A Biotechnology Approach for Microalgae Biomass - Astri Rinanti; Ronny Purwadi (Aceh International Journal of Science and Technology, 2018)
A study on Ankistrodesmus sp.—a freshwater green microalgae species—as a bioflocculant based on its physicochemical properties and flocculation rate has been carried out. The molecular identification via 16S rDNA showed 99% resemblance of this green microalga to the Ankistrodesmus fumigatus strain. The optimum batch culture condition for the bioflocculant production was initiated by 10% inoculum (v/v). The low-concentrated bioflocculant of 10% (v/v) is considered as thermostable with a high flocculation rate to harvest the biomass of Chlorella sp. at a pH range of 5 to 9. The source of molasses, the mixture of yeast extract were used as the optimum sources of carbon and Ammonium sulfate were used as the optimum sources of nitrogen in the growth medium. Ankistrodesmus sp. bioflocculant has a high flocculation efficiency over a wide range of pH (5–9) with a low dose requirement of 10% v/v at 25°C. Hence, it is immensely competitive to promote the economic viability of the production process. Accordingly, Ankistrodesmus sp. bioflocculant has a high potential to be applied on an industrial scale in tropical regions as it does not require additional production cost.